Developing Computational Thinking Skills Through a Text-Based Programming Approach: A Conceptual Framework - Zahari, Fariza; Mohamad Ali, Ahmad Zamzuri (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
Computational thinking has been identified as a fundamental requirement within 21st-century education curricula. It encompasses systematic problem analysis and the development of algorithmic solutions to address problems efficiently. Prior studies have predominantly focused on unplugged activities and Programming Assistance Tools (PATs), such as Alice and Scratch, in the development of computational thinking skills. However, empirical investigations examining the effectiveness of computational thinking within text-based programming environments remain limited. This study aims to develop a conceptual framework that integrates both theoretical and practical dimensions in the teaching of computational thinking, while also evaluating the effectiveness of two text-based programming languages: Python and C++ in enhancing these skills. The construction of this framework is grounded in two key models: Model of Learning Computational Thinking, which emphasizes cognitive development, and Programming in Seven Steps, which focuses on structured programming strategies. As a result, an integrative conceptual framework is proposed to support a more structured and reflective teaching and learning process. This framework is expected to inform future research and curriculum development initiatives related to the cultivation of computational thinking skills, particularly within text-based programming contexts.